2013
DOI: 10.1002/mds.25779
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐synuclein in the appendiceal mucosa of neurologically intact subjects

Abstract: Parkinson's disease is characterized by the pathological aggregation of Alpha-synuclein. The dual-hit hypothesis proposed by Braak implicates the enteric nervous system as an initial site of α-synuclein aggregation with subsequent spread to the central nervous system. Regional variations in the spatial pattern or levels of α-synuclein along the enteric nervous system could have implications for identifying sites of onset of this pathogenic cascade. We performed immunohistochemical staining for α-synuclein on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 46 publications
9
98
1
Order By: Relevance
“…Our observations are in line with Gray and colleagues, indicating that all neurologically intact subjects display αS-IR in their ganglion cell population [12]. Previous reports have reported αS-IR in none or in 8% to 82% of the neurologically intact subjects [11][12][13][14][15]. This discrepancy is related to the different antibodies used, different material assessed, i.e., surgical vs. post-mortem samples and the type of the sample, i.e., full thickness surgical sample vs. superficial endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are in line with Gray and colleagues, indicating that all neurologically intact subjects display αS-IR in their ganglion cell population [12]. Previous reports have reported αS-IR in none or in 8% to 82% of the neurologically intact subjects [11][12][13][14][15]. This discrepancy is related to the different antibodies used, different material assessed, i.e., surgical vs. post-mortem samples and the type of the sample, i.e., full thickness surgical sample vs. superficial endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Physiological 42/αS-IR was observed in the lamina propria, the submucosa, and particularly in the numerous ganglion cells of the myenteric plexus. Our observations are in line with Gray and colleagues, indicating that all neurologically intact subjects display αS-IR in their ganglion cell population [12]. Previous reports have reported αS-IR in none or in 8% to 82% of the neurologically intact subjects [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found several cases with staining of epithelial cells of gastric glands that was considered to be a nondisease‐related cross‐reaction to some secretory protein or enzymes of the gastric mucosa 33. Cellular elements detected, on the other hand, could represent mucosal macrophages ingesting pathological aSyn but their role in PD pathogenesis remains to be established 18. Therefore, the detection of non‐neuronal aSyn does not necessarily indicate a disease state.…”
Section: Discussionmentioning
confidence: 97%
“…It has, however, become increasingly apparent that the high sensitivity and specificity of GI aSyn detection to identify PD patients reported in the earlier studies 12, 13, 14, 15, 16 has not been sustained in subsequent studies repeatedly detecting aSyn accumulation also in the GI tract of neurologically healthy individuals 17, 18, 19, 20, 21. This was also confirmed by a recent multicentre study, which showed limited diagnostic value for detecting aSyn deposition in the GI biopsies by immunohistochemistry (IHC) 22.…”
Section: Introductionmentioning
confidence: 99%